Shaun the Sheep. A woolly good time [videorecording (DVD)] - Sadler, Christopher, 1970-; Park, Nick (Distributed by Lionsgate, 2010)
A little pinch of zaniness and a big dash of fun is the perfect recipe for laughter as Shaun and his barnyard buddies Bitzer, Shirley, and Timmy get into more wacky shenanigans along with those fun-loving Naughty Pigs next door.